2019
DOI: 10.1001/jamasurg.2018.4221
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Prophylactic Intraperitoneal Mesh Implantation for Prevention of Incisional Hernia in Patients Undergoing Open Abdominal Surgery

Abstract: is a frequent complication after open abdominal surgery. Prophylactic mesh implantation in the onlay or sublay position requires dissection of the abdominal wall, potentially leading to wound-associated complications. OBJECTIVE To compare the incidence of incisional hernia among patients after prophylactic intraperitoneal mesh implantation with that among patients after standard abdominal closure. DESIGN, SETTING, AND PARTICIPANTS An open-label randomized clinical trial was performed in 169 patients undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 39 publications
1
51
0
9
Order By: Relevance
“…IH remains a significant complication of abdominal incision and carries a considerable morbidity [4]. A recent randomised control trial demonstrated a significant reduction in incidence of IH when mesh was used to close elective laparotomies [41], which is supported by a 2017 meta-analysis [6]. However, evidence suggests an increase in chronic pain, post-operative seroma formation and delayed wound healing with mesh closure of elective laparotomies [6,42].…”
Section: Discussionmentioning
confidence: 99%
“…IH remains a significant complication of abdominal incision and carries a considerable morbidity [4]. A recent randomised control trial demonstrated a significant reduction in incidence of IH when mesh was used to close elective laparotomies [41], which is supported by a 2017 meta-analysis [6]. However, evidence suggests an increase in chronic pain, post-operative seroma formation and delayed wound healing with mesh closure of elective laparotomies [6,42].…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] Studies on prophylactic mesh have either not mentioned the FD incidence or had few cases, preventing the demonstration of a significant difference between the groups with and without mesh. [17][18][19][20][21][23][24][25][26] The reduced number of FDs can be explained because most studies included only patients undergoing elective procedures. 15,16,27 In addition, mesh application is still controversial in emergency laparotomy and in cases of contaminated and infected operations.…”
mentioning
confidence: 99%
“…In Kohler's recent publication there was increased early postoperative pain and prolonged wound healing of surgical site infection in those having mesh. While the pain difference in those who received mesh was confined to the early post-operative period long term trunk extension was reduced in those receiving a mesh [37].…”
Section: Current Limitationsmentioning
confidence: 94%
“…Trunk extension was significantly decreased after mesh implantation compared with the control group. A trend towards increased chronic pain after mesh implantation has been reported in the past [37].…”
Section: Problems With Mesh Insertionmentioning
confidence: 96%
See 1 more Smart Citation